Medical entomology for students - Service, M. W. (London : Chapman & Hall, 1996)
Arthropod vectors of disease pose major health problems worldwide. This textbook aims to provide the reader with basic information on the recognition, biology and medical importance of arthropods which affect human health and their control. The book is primarily aimed at students of subjects as diverse as tropical medicine, parasitology, entomology and pest control. It is also intended as a source of information for physicians, nurses, health officials and community health workers.
Easy accessibility, beautiful illustrations and clear presentation combine to make this book essential reading for students and teachers alike of this important subject.
1. 2. 3. Culicine mosquitoes (Culicinae) -- 4. Blackflies (Simuliidae) -- 5. Phlebotomine sandflies (Phlebotominae) -- 6. Biting midges (Certopogonidae) -- 7. Horseflies (Tabanidae) -- 8. Tsetse-flies (Glossinidae) -- 9. House-flies and stable-flies (Muscidae) and latrine flies (Fanniidae) -- 10. Flies and myiasis -- 11. Fleas (Siphonaptera) -- 12. Lice (Anoplura) -- 13. Bedbugs (Cimicidae) -- 14. Triatomine bugs (Triatominae) -- 15. Cockroaches (Blattaria) -- 16. Soft ticks (Argasidae) -- 17. Hard ticks (Ixodidae) -- 18. Scabies mites (Sarcoptidae) -- 19. Scrub typhus mites (Trombiculidae) -- 20. Miscellaneous mites.
Includes bibliographical references and index.
Keywords: Insects as carriers of disease; Entomology; Insect Vectors -- parasitology; Entomology